2012
DOI: 10.1016/j.rse.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Global estimation of evapotranspiration using a leaf area index-based surface energy and water balance model

Abstract: openAccessArticle: FalsePage Range: 581-581doi: 10.1016/j.rse.2012.06.004Harvest Date: 2016-01-12 15:13:54issueName:cover date: 2012-09-01pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 102 publications
6
154
0
2
Order By: Relevance
“…As soil data, including soil depth and soil texture, are used to calculate soil water characteristics so as to estimate actual E based on Air-Relative-humidity-based Two-Source (ARTS) E model (Yan et al, 2012), only 18 flux sites with available soil data were selected from AmeriFlux flux tower sites and measured GPP, E, and meteorological data by the eddy covariance (EC) method were used in this study. The EC method is regarded as the best method to directly measure fluxes (Paw et al, 2000) and has been widely applied to global CO 2 , water, energy measurements at flux tower sites in FLUXNET ).…”
Section: Eddy Covariance Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As soil data, including soil depth and soil texture, are used to calculate soil water characteristics so as to estimate actual E based on Air-Relative-humidity-based Two-Source (ARTS) E model (Yan et al, 2012), only 18 flux sites with available soil data were selected from AmeriFlux flux tower sites and measured GPP, E, and meteorological data by the eddy covariance (EC) method were used in this study. The EC method is regarded as the best method to directly measure fluxes (Paw et al, 2000) and has been widely applied to global CO 2 , water, energy measurements at flux tower sites in FLUXNET ).…”
Section: Eddy Covariance Datamentioning
confidence: 99%
“…MOD15A2C5 LAI/ FPAR products refine the obvious overestimation of LAI in old collection 4 (C4) LAI products . In the TEC algorithm, MODIS FPAR was directly applied to estimating GPP while MODIS LAI was only related to actual E retrieval by using ARTS E model (Yan et al, 2012).…”
Section: Modis Lai/fpar Products (Mod15a2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have quantified the spatial patterns of AET at regional (e.g., Li et al, 2014;Liu et al, 2013a;Wang et al, 2013) and global scales (e.g., Mu et al, 2011;Yan et al, 2012;Yuan et al, 2010) using process-based or remote sensing models. Although the spatial patterns described by different models generally agreed well with each other for a given region (Mueller et al, 2011;Liu et al, 2013a), large obvious uncertainties in AET values still remain.…”
Section: Introductionmentioning
confidence: 99%
“…The ARTS E 0 module and the simple snowmelting module in section 2.1 are adopted from ARTS E model [Yan et al, 2012]. The self-calibrating PDSI model [Wells et al, 2004] used in this study can be found in Appendix A (Calculation of Self-Calibrating PDSI model).…”
Section: Arts Pdsi Modelmentioning
confidence: 99%